2020
DOI: 10.1101/2020.11.13.20231373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysregulated immunity in SARS-CoV-2 infected pregnant women

Abstract: ImportanceThe effects of SARS-CoV-2 infection on immune responses during pregnancy have not been systematically evaluated.ObjectiveTo assess the impact of SARS-CoV-2 infection during pregnancy on inflammatory and humoral responses in maternal and fetal samples and compare antibody responses to SARS-CoV-2 among pregnant and non-pregnant women.DesignImmune responses to SARS-CoV-2 were analyzed using samples from pregnant and non-pregnant women who had either tested positive or negative for SARS-CoV-2. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
1
29
1
1
Order By: Relevance
“…In a recent pre-print, Sherer et al. reported that pregnant individuals with COVID-19 generated the same level of anti-S protein IgG but lower levels of anti-RBD IgG compared to individuals that were not pregnant [ 29 ]. Pregnant individuals with COVID-19 were less likely to have detectable neutralizing antibodies against SARS-CoV-2 than those that were not pregnant, suggesting that the quality of the antibody response against SARS-CoV-2 during pregnancy was inferior.…”
Section: Maternal Antibody Response To Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent pre-print, Sherer et al. reported that pregnant individuals with COVID-19 generated the same level of anti-S protein IgG but lower levels of anti-RBD IgG compared to individuals that were not pregnant [ 29 ]. Pregnant individuals with COVID-19 were less likely to have detectable neutralizing antibodies against SARS-CoV-2 than those that were not pregnant, suggesting that the quality of the antibody response against SARS-CoV-2 during pregnancy was inferior.…”
Section: Maternal Antibody Response To Sars-cov-2mentioning
confidence: 99%
“…Sherer et al. reported that while the level of SARS-CoV-2 S protein IgG was the same in maternal serum compared to umbilical cord blood, the level of neutralizing antibodies was reduced in the umbilical cord blood [ 29 ]. However, both the expression of FcRn in the placenta and the transfer of anti-tetanus IgG in pregnant individuals with and without COVID-19 was the same.…”
Section: Maternal Antibody Response To Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage in the pandemic, there is limited evidence regarding the immune response to COVID-19 during pregnancy, postpartum, breastfeeding, and in neonates. None of the completed or ongoing phase 3 clinical studies of vaccines include pregnant women (108), and further research is needed to understand the immune response in these special populations.…”
Section: Immunity In Special Populationsmentioning
confidence: 99%